2009
DOI: 10.1097/moo.0b013e32832ad23d
|View full text |Cite
|
Sign up to set email alerts
|

Localized immunoglobulin E expression in allergic rhinitis and nasal polyposis

Abstract: Increased levels of IgE have been identified in sinonasal tissues in allergic and nonallergic rhinitis, atopic and nonatopic sinonasal polyposis, and allergic fungal rhinosinusitis. The ability to identify local tissue IgE in inflammatory sinonasal disease states may have significant diagnostic and therapeutic implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
26
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 38 publications
5
26
0
Order By: Relevance
“…Interleukin (IL)-4, IL-13, and CD40, the necessary elements for IgE production, also have been detected within sinonasal tissue. Inferior turbinate tissue from patients with known allergy to grass pollen was studied after antigen exposure in vitro and found to have an increase in IL-4 RNA and germline ε gene exons, which are spliced out during immunoglobulin class-switching gene recombination [33,34]. Takhar et al [35] showed that both in vitro and in vivo exposure to grass pollen in allergic patients stimulates production of circle transcripts, a marker of ongoing class-switching, and that class-switch recombination to IgE from multiple other isotypes occurs in the sinonasal mucosa.…”
Section: Initial Studies Of Local Ige In the Airwaysmentioning
confidence: 99%
“…Interleukin (IL)-4, IL-13, and CD40, the necessary elements for IgE production, also have been detected within sinonasal tissue. Inferior turbinate tissue from patients with known allergy to grass pollen was studied after antigen exposure in vitro and found to have an increase in IL-4 RNA and germline ε gene exons, which are spliced out during immunoglobulin class-switching gene recombination [33,34]. Takhar et al [35] showed that both in vitro and in vivo exposure to grass pollen in allergic patients stimulates production of circle transcripts, a marker of ongoing class-switching, and that class-switch recombination to IgE from multiple other isotypes occurs in the sinonasal mucosa.…”
Section: Initial Studies Of Local Ige In the Airwaysmentioning
confidence: 99%
“…Clinical studies have found a close association between asthma and serum IgE levels, and the amount of allergen-specific IgE can be dramatically increased in sensitized or atopy patients (7,8). Allergen-specific IgE is located in the human airway, such as in nasal mucosa from allergic patients who suffer allergic rhinitis in sinonasal tissue, nasal polyposis, and allergic fungal rhinosinusitis (9)(10)(11)(12). This observation is further supported by the fact that B cells from the nasal mucosa of allergic individuals locally synthesize IgE (13,14).…”
mentioning
confidence: 99%
“…Patients with AFRS frequently exhibit positive reactions to multiple fungal and nonfungal antigens, guiding subsequent allergen-specific immunotherapy. 32,[37][38][39][40][41] There is a subset of patients, however, who demonstrate the classic features of AFRS, but do not exhibit elevated systemic levels of total IgE. 32,42 In a 2004 study, Collins and colleagues 43 investigated a phenomenon termed ''entopy,'' or increased local IgE in the absence of systemic disease in AFRS.…”
Section: Local Ige: Intranasal Elevated Ige In Nasal Tissuesmentioning
confidence: 97%
“…31 In 1970, Tse and colleagues demonstrated ragweed-specific IgE in nasal washings of ragweed-allergic patients with allergic rhinitis, providing additional evidence for local antigen-specific IgE in nasal mucosa. [31][32][33] In a 1974 study by Huggins and Brostoff, 34 patients with typical allergic rhinitis symptoms with both positive and negative systemic allergy tests, as well as patients free from any allergic symptoms, were exposed to grasspollen extract intranasally. Subsequent nasal washings revealed elevated grass pollen-specific IgE in all patients with allergic rhinitis regardless of systemic allergy test status, when compared with nonallergic controls, suggesting local intranasal IgE production.…”
Section: Local Ige: Intranasal Elevated Ige In Nasal Tissuesmentioning
confidence: 99%